2010
DOI: 10.1074/jbc.m110.113696
|View full text |Cite
|
Sign up to set email alerts
|

Nonamyloid Aggregates Arising from Mature Copper/Zinc Superoxide Dismutases Resemble Those Observed in Amyotrophic Lateral Sclerosis

Abstract: Protein aggregation is a hallmark of many diseases, including amyotrophic lateral sclerosis (ALS) where aggregation of copper/zinc superoxide dismutase (SOD1) is implicated in pathogenesis. We report here that fully metallated (holo) SOD1 under physiologically relevant solution conditions can undergo changes in metallation and/or dimerization over time and form aggregates that do not exhibit classical characteristics of amyloid. The relevance of the observed aggregation to disease is demonstrated by structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 95 publications
4
61
0
Order By: Relevance
“…Other forms of SOD1 have also been shown previously to form amyloid under destabilizing conditions caused by denaturant, sonication, trifluoroethanol, or low pH (8,14,20,40), and formation of intermolecular disulfide bonds (25). In contrast, other studies under less extreme conditions have also reported evidence for distinct aggregation processes from native-like states (41)(42)(43). Protein aggregation is generally strongly dependent on solution conditions, and many destabilizing and often nonphysiological conditions can result in the formation of amyloid.…”
Section: In the Absence Of Als-associated Mutations Reduced Apo Sod1mentioning
confidence: 81%
“…Other forms of SOD1 have also been shown previously to form amyloid under destabilizing conditions caused by denaturant, sonication, trifluoroethanol, or low pH (8,14,20,40), and formation of intermolecular disulfide bonds (25). In contrast, other studies under less extreme conditions have also reported evidence for distinct aggregation processes from native-like states (41)(42)(43). Protein aggregation is generally strongly dependent on solution conditions, and many destabilizing and often nonphysiological conditions can result in the formation of amyloid.…”
Section: In the Absence Of Als-associated Mutations Reduced Apo Sod1mentioning
confidence: 81%
“…Accordingly, it has been shown that the in vitro fibrillation of apoSOD1 displays the characteristic fingerprint of fragmentation-assisted growth (15) with a square root dependence on [D] (7), consistent with the requirement of sample agitation to expedite the reaction (1)(2)(3)(4)10). Analogous fibrillation behavior is found for β2-microglobulin (2), yeast prions Sup35 (16) and Ure2p (17), insulin (18), WW domain (19), TI 127 (20), and α-synuclein (21).…”
mentioning
confidence: 72%
“…A number of studies have used different solution conditions (increased temperature, decreased pH, increased ionic strength, sonication or agitation) to promote the formation of well-structured, fibrillar amyloid aggregates (see 1.2.3) by various forms of SOD1 (Stathopulos et al 2004;Chattopadhyay et al 2008;Chattopadhyay and Valentine 2009;Oztug Durer et al 2009). Other studies have demonstrated soluble oligomer and small aggregate formation by various forms of SOD1 in quiescent, physiologically relevant solution conditions (Vassall, 2011, Hwang, 2010, Banci, 2008. Thus, it is evident that multiple factors can greatly influence protein folding and aggregation and these factors must be considered when investigating the molecular mechanisms of protein aggregation.…”
Section: Factors That Modulate Aggregation Of Polypeptidesmentioning
confidence: 99%
“…The overwhelming majority of fALS-associated mutations destabilize the holo state, but because of its extremely high thermodynamic stability the absolute increase in the amount of unfolded species will still be very small, and thus unlikely to affect aggregation. What seems more likely to impact disease is increased local structural fluctuations that can arise from www.intechopen.com metal loss and/or dimer dissociation, exposing regions of the SOD1 structure that can make favourable contacts with other SOD1 molecules, and thereby give rise to aggregation from native-like states (Elam et al 2003;Hwang et al 2010). …”
Section: Equilibrium Denaturation Of Holos-s Sod1mentioning
confidence: 99%
See 1 more Smart Citation